Predictors of improved nutritional status among HIV/AIDS patients who received antiretroviral therapy (ART) at Sanglah General Hospital Denpasar - Gusti Ayu Eka Utarini; Anak Agung Sagung Sawitri; Ketut Tuti Parwati Merati (Universitas Udayana, 2017)
Background and purpose: Antiretroviral therapy (ART) is associated with improved nutritional status among HIV/AIDS patients. This study aims to examine proportion, median time, incidence rate, and predictors of improved nutritional status among HIV/AIDS patients who received ART at Sanglah General Hospital Denpasar. Methods: A restrospective cohort study was conducted in Denpasar City. A total of 207 medical records of HIV/AIDS patients who received ART between 1st of January 2012 and 30th of June 2015 were included in the study. Kaplan Meier analysis was performed to calculate incidence rate and median time of improved nutritional status among HIV/AIDS patients. Sociodemographic characteristics and clinical variables included body mass index (BMI), body weight, haemoglobin level, CD4 count, HIV clinical stadium, ART regiments, and opportunistic infections (OIs). Data were analysed using cox proportional hazard model to identify predictors of improved nutritional status among HIV/AIDS patients. Results: As many as 65.22% of HIV/AIDS patients who received ART experienced an improvement in their nutritional status with the incidence rate of 9.1 per 100 person months and median time of 6.1 months. Multivariate analysis showed that predictors of improved nutritional status were BMI at ART initiation (AHR=1.34; 95%CI: 1.16-1.5), HIV clinical stadium (AHR=1.45; 95%CI: 1.02-2.06), CD4 count at ART initiation (AHR=0.89; 95%CI: 0.81-0.99) and the presence of diarrhoea (AHR=1.83; 95%CI: 1.06-3.14). Conclusions: Predictors of improved nutritional status among HIV/AIDS patients who received ART were BMI, HIV clinical stadium, CD4 count and diarrhoea.